(untitled) (Bangladesh Journal of Zoology, 2024)
Malaria imparts significant public health concern in humanitarian emergency settings in endemic areas from a relatively more compromised and flaccid disease surveillance and monitoring practice compared to that in peace time situation. Incurring a chronically high malaria case morbidity and mortality Africa and south-east Asia additionally suffer from human caused conflict and war led population migration and displacement crises intermittently to exacerbate malaria burden in the two regions. The patterns and trends in the transmission dynamics of malaria infections in peace time and plain areas is considered to be complicated with in-country as well as cross-border human movement to and from the endemic and/or non-endemic territories. This ends in with developing imported or introduced plasmodial infections in an area that stands as the key challenge for controlling or eliminating malaria there. Then exploring malaria situation and experiences in some key refugee camps in Africa and south-east Asia in this review paper has helped us add new experiences and ideas of fighting malaria to the existing data base of the disease. The acute and unstable humanitarian settings in malaria endemic areas intrigue the disease transmission dynamics and the toll with greater fluctuation in terms of case morbidity and mortality compared with that in chronic and unstable humanitarian emergency situations. This and other overviews here will definitely better guide malaria elimination efforts, especially in humanitarian emergencies in the two endemic regions in an integrated and comprehensive way. Bangladesh J. Zool. 52(2): 141-166, 2024